PENGARUH BEBERAPA DOSIS LIMBAH PADAT PABRIK KELAPA SAWIT (SLUDGE) DAN PUPUK P TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMANBAWANG MERAH (Allium ascalonicum L.) - Tarigan, Pingko Abdianta; Armaini, Armaini; Murniati, Murniati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The aim of this research was to find out the effect of treatment of solid waste the palm oil mill (Sludge) and phosphates and getting the best treatment combination on the growth and productivity of shallot. This research was conducted on experimental farm, the Faculty of Agriculture, Riau University, Campus Bina Widya Km 12,5, sub-district of Simpang Baru, district of Tampan, Pekanbaru, from May until September 2016. The research design was randomized complete block design, factorial 4x2 and 3 replications. The first factor was solid waste the palm oil mill (5, 10, 15, and 20 ton. Ha-1) and the second factor was phosphates fertilizer (50 and 100 kgP2O5. Ha-1). Data results were analyzed statistically operates with anova and Duncan test continued level of 5%. The result of the research showed that the interaction of solid waste the palm oil mill and phosphates fertilizer have no effect to all of observed parameters significantly. The result revealed that the 20 tons. Ha-1 solid waste the palm oil mill with 50 kgP2O5. Ha-1 phosphates were better than other combination of treatments because the treatments showed the highest quantity. Keywords: Solid waste the palm oil mill, phosphates and Shallot.